Infectious Salmon Anemia Virus Infectivity Is Determined by Multiple Segments with an Important Contribution from Segment 5 - Montoya-Kunsting, M; Vasquez-Martinez, y; Cortez-San Martin, M; Michelson-Quintana, S (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Infectious salmon anemia virus (ISAV) is the etiological agent of infectious salmon anemia. It belongs to the genus isavirus, one of the genera of the Orthomyxoviridae family, as does Influen-zavirus A. The ISAV genome comprises eight negative-sense single-stranded RNA segments that code for at least 10 proteins. Although some ISAV strains can reach 100% mortality rates, the factors that determine isavirus infectivity remain unknown. However, some studies suggest that segments 5 and 6 are responsible for the different degrees of virulence and infectivity among ISAV subtypes, unlike the influenza A virus, where most segments are involved in the virus infectivity. In this work, synthetic reassortant viruses for the eight segments of ISAV were generated by reverse genetics, combining a highly virulent virus, ISAV 752_09 (HPR7b), and an avirulent strain, SK779/06 (HPR0). We characterized the rescued viruses and their capacity to replicate and infect different cell lines, produce plaques in ASK cells, and their ability to induce and modulate the cellular immune response in vitro. Our results show that the majority of ISAV segments are involved in at least one of the analyzed characteristics, segment 5 being one of the most important, allowing HPR0 viruses, among other things, to produce plaques and replicate in CHSE-214 cells. We determined that segments 5 and 6 participate in different stages of the viral cycle, and their compatibility is critical for viral infection. Additionally, we demonstrated that segment 2 can modulate the cellular immune response. Our results indicate a high degree of genetic compatibility between the genomic segments of HPR7b and HPR0, representing a latent risk of reassortant that would give rise to a new virus with an unknown phenotype. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: isavirus; salmonid; reverse genetic; infectivity